Analysis of Politeness Strategies in Mahmud Taymur’s Short Story “Thariqun ila Al-Hubb”: The Brown-Levinson Perspective - Lita Oktavya Wulan Syamhana; Abdullah Zainur Rauf (Hasanuddin University, 2025)
This study investigates the realisation of Brown and Levinson’s (1987) politeness strategies in the short story Thariqun ila Al-hub by Mahmud Taymur, focusing on how characters’ utterances reflect the four main strategies: bald on record, positive politeness, negative politeness, and off record. Using a descriptive qualitative approach, data were collected from the original Arabic text through careful reading and note-taking, followed by translation into Indonesian for analysis. The findings reveal that, out of 17 identified utterances, positive politeness is the most dominant strategy (47%), followed by negative politeness (24%), bald on record (18%), and off record (12%). The distribution varies across characters: some predominantly employ positive politeness to foster solidarity and closeness, while others rely on negative politeness to preserve distance and minimise face threats, and a few opt for directness (bald on record). These findings show that language politeness strategies not only serve to maintain social harmony but also serve as a means of expressing something, both in literary works and in real life.